–2518 A/G MCP-1 but not –403 G/A RANTES gene polymorphism is associated with enhanced risk of basal cell carcinoma - Sobjanek, Michał; Zabłotna, Monika; Szczerkowska-Dobosz, Aneta; Ruckemann-Dziurdzińska, Katarzyna; Sokolowska-Wojdylo, Malgorzata; Nowicki, Roman (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction : Polymorphic variants of MCP-1 and RANTES genes and their protein serum levels have been implicated in the increased risk and severity of several malignancies. However, the subject has not been explored in basal cell carcinoma (BCC) patients so far. Aim : To investigate the association between monocyte chemoattractant protein 1 (MCP-1) (–2518 A/G) and RANTES (–403 G/A) polymorphism and risk and clinical course of BCC. Material and methods : The study group consisted of 150 unrelated patients with BCC and 140 healthy, unrelated, age- and sex-matched volunteers. The polymorphisms were analysed using the amplification refractory mutation system polymerase chain reaction method (ARMS-PCR) and single specific primer-polymerase chain reaction (SSP-PCR). Serum cytokine levels were measured with ELISA. Results : The presence of the MCP-1 –2518 GG genotype was statistically more frequent in BCC patients and it increased the risk of BCC (OR = 2.63, p = 0.003). Genotype –330 GG was statistically more common in patients with less advanced tumours (OR = 2.8, p = 0.017). Monocyte chemoattractant protein 1 serum level was statistically higher with GG genotype. In the BCC group MCP-1 serum levels were decreased. Neither polymorphic variants of RANTES nor the chemokine serum concentration differed significantly between the study groups. Conclusions : These findings suggest that –2518 A/G MCP-1 polymorphism may be involved in BCC pathogenesis.